The impact of community pharmacists on older adults in Turkey - OKUYAN, BETÜL (ELSEVIER, 2021)
Objective: This study aimed to evaluate the impact of theory-based, structured, standardized pharmaceutical care services led by community pharmacists (CPs) on patient-related outcomes in older Turkish adults. Practice description: This prospective, quasi-experimental pilot study was conducted at the national level at community pharmacies in Turkey. After virtual training of CPs, pharmaceutical care services including medicine bag check-up, medication review, patient medicine card, patient education, and counseling services (including motivational interviewing) were delivered to promote medication adherence in older adults. Practice innovation: Theory-based, structured, standardized pharmaceutical care services addressing medication adherence problems in older Turkish adults with noncommunicable diseases. Evaluation Methods: Descriptive data (including demographic and clinical data, medication-related problems by using the DOCUMENT classification, potential inappropriate prescribing by using the Ghent Older People's Prescriptions Community Pharmacy Screening- (GheOP(3)S) tool, and pharmacy service satisfaction) were presented. Pre- and post-evaluation were compared by using the Wilcoxon test (for continuous variables) and McNemar's or McNemar-Bowker chi-square test (for categorical variables). Results: One hundred and thirty-eight medication-related problems were identified among 52 older adults. The medication adherence rate was significantly increased from 51.9% to 75%, and the mean of total quality of life (QoL) score rose significantly from 51.7 to 53.4 (P <0.05). There was a statistically significant change in the median of necessity-concern differential (baseline: 7 [2.2-10.0] vs. final: 8.0 [5-11]; P < 0.05). At baseline, all patients had at least 1 potential inappropriate prescribing according to the GheOP(3)S tool, and the rate was 73.1% at the final assessment. Conclusion: Community pharmacist-led pharmaceutical care services significantly improved patient-related outcomes (such as medication adherence, beliefs about medication, and QoL) in older adults with noncommunicable diseases. No statistically significant change was detected in their lifestyle behaviors (such as physical activity and diet program) or health awareness. (C) 2021 American Pharmacists Association (R). Published by Elsevier Inc. All rights reserved.
Keywords: RANDOMIZED CONTROLLED-TRIAL; QUALITY-OF-LIFE; MEDICINES QUESTIONNAIRE; PATIENT SATISFACTION; PHARMACEUTICAL CARE; CHRONIC DISEASES; MEDICATION; ADHERENCE; BELIEFS; MANAGEMENT